STUDY OF THE RELATIONSHIP BETWEEN THE PERCENTAGE OF FATTY ACIDS IN MILK´S FAT AND BLOOD PLASMA DURING THE STAGES OF MILK PRODUCTION IN HOLSTEIN-FRIESIAN COWS - Zainab S. Al-Obaidi; A. M. Dr. Muntaha Y. Yousief (European Journal of Agricultural and Rural Education, 2024)
The relationships between fatty acids in milk fat and the quality standards of milk production during the lactation phase are very weak in dairy cows. Therefore, the current study aimed to predict the correlation between the studied standards and the proportions of milk components through the contribution ratios of fatty acids and biochemical blood standards during different production stages. This study was conducted at the Taj Al Nahreen Cattle Station in Al-Qadisiyah Governorate. The cows were divided into three groups, from which 720 samples of cow’s milk were collected for a period of 90 days from Holstein-Friesian cows. Additionally, 360 blood samples were collected from 60 Holstein-Friesian cows to determine the biochemical traits. The fatty acid components were studied for the entire study period, and the results showed significant differences in the proportions of saturated and unsaturated fatty acids in blood plasma during the production stages. The proportion of saturated fatty acids in blood plasma increased compared to unsaturated fatty acids, depending on the production stages